2022
DOI: 10.1101/2022.07.21.500991
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Benzimidazoles cause lethality by inhibiting the function of Caenorhabditis elegans neuronal beta-tubulin

Abstract: Parasitic nematode infections cause an enormous global burden to both human and livestock populations. Resistance to the limited arsenal of anthelmintic drugs used to combat these infections is widespread, including resistance to benzimidazole (BZ) compounds commonly found in livestock parasites. Previous studies using the free-living nematode Caenorhabditis elegans to model parasitic nematode resistance have shown that loss-of-function mutations in the beta-tubulin gene ben-1 confer resistance to BZ drugs. Ho… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 62 publications
0
3
1
Order By: Relevance
“…Benzimidazoles are known to inhibit C. elegans and natural resistance to these compounds has arisen through genetic variation in betatubulin [57,58]. Host toxicity has been shown to be mediated through inhibition of neuronal betatubulin [59]. Carbendazim, fenbendazole and oxfendazole are present in the PRB, however, in our preliminary screening, we did not find that these compounds improved progeny production in the presence of N. parisii.…”
Section: Discussioncontrasting
confidence: 55%
“…Benzimidazoles are known to inhibit C. elegans and natural resistance to these compounds has arisen through genetic variation in betatubulin [57,58]. Host toxicity has been shown to be mediated through inhibition of neuronal betatubulin [59]. Carbendazim, fenbendazole and oxfendazole are present in the PRB, however, in our preliminary screening, we did not find that these compounds improved progeny production in the presence of N. parisii.…”
Section: Discussioncontrasting
confidence: 55%
“…To date, our understanding of the MoR and tissue-specific susceptibility for most anthelmintic drugs across nematode species is not well known. Previous research has shown that ben-1 is highly expressed in cholinergic neurons, which causes BZ susceptibility [42]. However, analogous experiments are imperative to ascertain in which tissues GluCl subunit genes underlie ivermectin susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…With its ease of growth, outstanding genetic tractability, and molecular toolkits, the free-living nematode Caenorhabditis elegans has contributed to the identification and characterization of the MoA and MoR of all major anthelmintic drug classes [27][28][29][30][31][32][33][34]. Additionally, wild C. elegans strains from the Caenorhabditis Natural Diversity Resource (CaeNDR) [35] have been used to explore anthelmintic resistance in natural populations and to uncover novel MoR [30,[35][36][37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With its ease of growth, outstanding genetic tractability, and molecular toolkits, the free-living nematode Caenorhabditis elegans has contributed to the identification and characterization of the Mode of Action (MoA) and MoR of all major anthelmintic drug classes [33][34][35][36][37][38][39][40]. Additionally, wild C. elegans strains from the Caenorhabditis Natural Diversity Resource (CaeNDR) [41] have been used to explore anthelmintic resistance in natural populations and to uncover novel MoR [36,[41][42][43][44][45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%